PENGARUH KOMPOS JERAMI PADI DENGAN DEKOMPOSER Trichoderma sp. TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG MANIS DI LAHAN ULTISOL - iwanto, iwanto (Fakultas Pertanian Universitas Tanjungpura, 2016)
ABSTRACK Rice straw is one of the agricultural waste as a potential enhancer nutrients in the soil. To speed up the composting process are treated the role of microorganisms such as Trichoderma sp. the objective of this study is determine the effect of rice straw compost with decomposers Trichoderma sp. the growth and yield of sweet corn on the ground ultisol Village Nyangau Ella Hilir Subdistrict Melawi. The study was conducted from July 2015 until November 2015. This study uses a RAL is composed of 5 treatments and 5 replicates, the study was conducted in the field by making treatment experimental plots of 3.5 m x 1 m. these treatments were coded K0 (without composting rice straw), K1 (straw compost 10 tons / ha), K2 (composted rice straw 20 tons / ha), K3 (composted rice straw 30 tons / ha) and K4 (composted rice straw 40 tons / ha). The results showed that administration of rice straw compost affect the growth of corn plants but has no effect on crops such as sweet corn cob weight, ear length and cob diameter.